A SiC@C integrated composite photoanode and its preparation method and application

Through the SiC@C integrated composite photoanode, combined with SiC nanopore array and amorphous carbon nano-thin layer, the bottlenecks and composite modification problems of photoanode catalyst materials are solved, and efficient photoelectrocatalytic performance and industrial applications are achieved.

CN115044926BActive Publication Date: 2025-01-14NINGBO UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210597047.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-30
Publication Date
2025-01-14
Estimated Expiration
2042-05-30

AI Technical Summary

Technical Problem

The performance of existing photoanode catalyst materials has approached the theoretical level. The catalytic activity of catalyst materials in a single material system has encountered bottlenecks, there are few researches on hole storage layer materials, and there are great problems in composite modification of nanopore structures, which limits its industrial application.

Method used

Using SiC@C integrated composite photoanode, including SiC nanopore array layer and amorphous carbon nanolayer deposited on its surface, the pore size and carbon nanolayer thickness are controlled by chemical vapor deposition method to form excellent charge transport characteristics and light absorption characteristic.

Benefits of technology

It achieves high photoelectric catalytic performance, low starting potential, high photocurrent density and excellent photoconversion efficiency, provides a reliable development path for clean energy, and simplifies the preparation method for industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115044926B_ABST
    Figure CN115044926B_ABST
Patent Text Reader

Abstract

The present invention relates to a SiC@C integrated composite photoanode and a preparation method and application thereof, belonging to the field of photoelectrochemical technology. The present invention discloses a SiC@C integrated composite photoanode, the SiC@C integrated composite photoanode comprising a SiC nanopore array layer and a carbon nanothin layer deposited on the surface thereof. The present invention also discloses a preparation method of a SiC@C integrated composite photoanode, the preparation method comprising: chemically vapor depositing polymethyl methacrylate and a SiC photoanode semi-finished product in a dual-temperature zone tubular furnace.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoelectrochemistry and relates to a SiC@C integrated composite photoanode and a preparation method and application thereof. Background Art

[0002] The development of clean energy and the study of the replacement of traditional energy have become a consensus issue worldwide. The development of clean energy such as electricity and hydrogen energy has become a general trend. After the Paris Climate Summit, all countries have also introduced clean energy development policies and proposed carbon neutrality goals. The conversion of renewable energy solar energy into hydrogen energy is a promising way to develop clean energy. Its key technical path, photoelectrochemical water splitting technology, is also being widely studied. The water oxidation catalytic reaction of the photoanode in the two half reactions of water splitting becomes the rate-limiting reaction of the overall water splitting reaction due to its four-electron reaction process. Therefore, the research on photoanode catalyst materials is also crucial. Photoanode materials including silicon carbide, titanium dioxide, bismuth vanadate, etc. have been deeply studied. However, the research on the performance of common photoanodes has approached and reached its theoretical level, and the research on the catalytic activity of catalyst materials for single material systems has encountered bottlenecks.

[0003] At present, the common modification methods of photoanode semiconductor catalyst materials mainly include developing hole storage layers, semiconductor doping, forming homojunctions, constructing heterojunctions, composite co-catalysts, and a combination of multiple methods. The introduction of the hole storage layer provides an effective way to separate and transport photogenerated charges and promote surface reactions. The research on hole transport storage layers mainly includes black scales and carbon materials. Most of their design ideas are aimed at the surface composite process of nano-bulk materials. Due to the limitations of the composite material structure, harsh experimental conditions, and difficult preparation methods, the promotion and implementation of its industrial application are severely restricted.

[0004] At present, researchers have made great progress in the research of photoanodes such as silicon carbide. However, in the research of photoanode catalytic materials for industrial application, there are still several key issues to be studied and resolved: First, the research on the composite modification process of single-system catalyst materials still needs to be expanded; second, there is little research on hole storage layer materials used for composite modification of catalyst surfaces to facilitate the storage and transport of photogenerated carriers; third, catalyst materials with nanoporous structures have excellent light absorption characteristics, but their composite modification is relatively challenging and rarely reported. Summary of the invention

[0005] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and to propose a SiC@C integrated composite photoanode having a hole storage layer material with excellent photocatalytic performance and facilitating the storage and transport of photogenerated carriers.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A SiC@C integrated composite photoanode comprises a SiC nano-hole array layer and a carbon nano-thin layer deposited on the surface of the SiC@C integrated composite photoanode.

[0008] Preferably, the pore size distribution of the SiC@C integrated composite photoanode is 40-60 nm.

[0009] More preferably, the pore size distribution of the nanopore array structure without deposited carbon nanofilm is 50-70 nm.

[0010] After deposition, the carbon nanolayer will be on the nanopore wall, so the pore size will be reduced. The pore size of the SiC@C integrated composite photoanode of the present invention is 40-60nm. Excessive carbon deposition causes the pore size of the nanopore structure to become smaller, causing the photoelectrocatalytic performance of the composite photoanode to be attenuated to a certain extent; insufficient carbon deposition leads to too few carbon nanolayers, resulting in poor photoelectrocatalytic performance.

[0011] Preferably, the thickness of the carbon nanofilm is 2-5 nm.

[0012] The direct factor affecting thickness and pore size is deposition time, so it is necessary to control deposition time so that the carbon deposition thickness is 2-5nm and the pore size distribution is 40-60nm. Under the condition of balancing the electrolyte flow and the thickness of the hole transport storage layer, the catalytic performance increases with the deposition time. However, excessive deposition will cause the pore size of the nanopore structure to become smaller and the thickness to be too large, hindering the flow of the electrolyte, thereby attenuating the photoelectrocatalytic performance. Insufficient carbon deposition will result in too few carbon nanothin layers and poor photoelectrocatalytic performance.

[0013] Preferably, the carbon nanothin layer is amorphous carbon.

[0014] Amorphous carbon is formed by carbon elements in different hybrid states and has excellent charge transport properties, which is beneficial to the storage and transport of photogenerated carriers.

[0015] The present invention also discloses a method for preparing a SiC@C integrated composite photoanode, the preparation method comprising: subjecting polymethyl methacrylate (PMMA) and a SiC photoanode semi-finished product to chemical vapor deposition in a dual-temperature zone tubular furnace.

[0016] The deposition process of the present invention needs to be carried out in a dual-temperature zone tubular furnace. This is because the deposition temperature of the SiC photoanode semi-finished product needs to be controlled. If the temperature is too high, deposition is difficult, and if the temperature is too low, deposition is uncontrolled. A single-temperature tubular furnace cannot control the deposition temperature on silicon carbide.

[0017] Preferably, the amount of polymethyl methacrylate added is 180-220 mg, and the size of the SiC photoanode semi-finished product is (0.5-1.5) cm×1.5 cm.

[0018] Preferably, the polymethyl methacrylate is located in the high temperature zone of a dual-temperature zone tubular furnace, and the SiC photoanode semi-finished product is located in the low temperature zone of the dual-temperature zone tubular furnace, and the heating time is 5-30 minutes.

[0019] Preferably, the temperature of the high temperature zone is 140-190°C, and the temperature of the low temperature zone is 40-65°C.

[0020] More preferably, the heating time of the high temperature zone and the low temperature zone is the same.

[0021] More preferably, the heating rate of the high temperature zone is 0.5-2°C / min.

[0022] Preferably, the preparation of the SiC photoanode semi-finished product comprises: etching and stripping the cap layer and etching the nanopore structure in sequence on the cleaned 4H-SiC single crystal and graphite sheet in an etching solution.

[0023] Further preferably, the etching solution is a mixed solution of HF, C2H5OH and H2O2 in a volume ratio of (5-7):(5-7):1.

[0024] Further preferably, the anodization etching process includes decapping and stripping and nanopore structure etching, specifically, the cap layer etching voltage is a pulse voltage of 20-22V, the duration is 0.8-0.9min, the application period is 0.7-0.9s, and the dwell time is 1 / 2 of the application period, and the subsequent stripping process applies a constant voltage of 28-32V, the duration is 0.1-0.2min; the nanopore structure etching is continuous periodic etching, the etching voltage is a pulse voltage of 18-20V, the application period is 0.7-0.9s, the dwell time is 1 / 2 of the application period, and the duration is 9-11min.

[0025] Preferably, the anodic oxidation etching uses a DC power analyzer as an electrochemical etching power source.

[0026] The invention also discloses the application of a SiC@C integrated composite photoanode in the field of photocatalysis.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. An amorphous carbon nano-thin layer is deposited on the surface of the SiC@C integrated composite photoanode of the present invention. The amorphous carbon nano-thin layer serves as a hole transport storage layer and is tightly coated on the surface of the SiC nano-pore wall. On the one hand, its excellent charge transport properties ensure the efficient absorption properties of the nano-pore array structure for visible light; on the other hand, it promotes the transmission of photogenerated carriers in the SiC bulk phase. The photogenerated holes stored in the carbon nano-thin layer further inhibit the recombination of photogenerated carriers on the catalyst surface, effectively reducing the carrier recombination rate.

[0029] 2. The present invention adjusts the chemical vapor deposition to make the pore size distribution 40-60nm, which is beneficial to increase the photoelectrocatalytic performance; the thickness of the amorphous carbon nanofilm is maintained at 2-5nm, which is beneficial to balance the circulation of the electrolyte and the thickness control of the hole transport storage layer.

[0030] 3. The SiC@C integrated composite photoanode of the present invention has a low starting potential, a high photocurrent density and excellent light conversion efficiency. The combined excellent photoelectrocatalytic properties provide a reliable candidate path for the effective use of solar energy to prepare clean energy.

[0031] 4. The preparation method of the present invention is simple, controllable and easy to operate.

[0032] 5. The SiC@C integrated composite photoanode of the present invention is applied to the field of photocatalysis and has excellent catalytic water decomposition reaction.

[0033] Instruction Manual

[0034] Figure 1 This is a surface scanning electron microscope (SEM) image of the SiC@C integrated composite photoanode prepared in Example 1 of the present invention.

[0035] Figure 2 This is a transmission electron microscope (TEM) image of the nanopore structure of the SiC@C integrated composite photoanode prepared in Example 1 of the present invention.

[0036] Figure 3 This is a Raman spectrum diagram of the SiC@C integrated composite photoanode prepared in Example 1 of the present invention.

[0037] Figure 4 This is a linear voltammetric sweep curve (LSV) diagram of the SiC@C integrated composite photoanode prepared in Example 1 of the present invention.

[0038] Figure 5 This is a graph of the light conversion efficiency (ABPE) of the SiC@C integrated composite photoanode prepared in Example 1 of the present invention.

[0039] Figure 6This is a surface scanning electron microscope (SEM) image of the SiC@C integrated composite photoanode prepared in Example 2 of the present invention.

[0040] Figure 7 This is a linear voltammetric sweep curve (LSV) diagram of the SiC@C integrated composite photoanode prepared in Example 2 of the present invention.

[0041] Figure 8 This is a graph of the light conversion efficiency (ABPE) of the SiC@C integrated composite photoanode prepared in Example 2 of the present invention.

[0042] Fig. 9 This is a surface scanning electron microscope (SEM) image of the SiC@C integrated composite photoanode prepared in Example 4 of the present invention.

[0043] Fig.10 This is a linear voltammetric sweep curve (LSV) diagram of the SiC@C integrated composite photoanode prepared in Example 4 of the present invention.

[0044] Fig.11 This is a graph of the light conversion efficiency (ABPE) of the SiC@C integrated composite photoanode prepared in Example 4 of the present invention.

[0045] Fig.12 This is a surface scanning electron microscope (SEM) image of the SiC@C integrated composite photoanode prepared in Comparative Example 2 of the present invention.

[0046] Fig.13 This is a linear voltammetric sweep curve (LSV) diagram of the SiC@C integrated composite photoanode prepared in Comparative Example 2 of the present invention.

[0047] Fig.14 This is a graph of the light conversion efficiency (ABPE) of the SiC@C integrated composite photoanode prepared in Comparative Example 2 of the present invention.

[0048] Fig.15 The linear voltammetric scanning curve (LSV) diagram of the SiC@C integrated composite photoanode prepared in Examples 1, 2, 4 and Comparative Example 2 of the present invention.

[0049] Fig.16 This is a graph of the light conversion efficiency (ABPE) of the SiC@C integrated composite photoanode prepared in Examples 1, 2, 4 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0050] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.

[0051] Example 1

[0052] The preparation of the SiC photoanode semi-finished product is as follows: 4H-SiC single crystal (commercial 4H-SiC single crystal purchased from Shanxi Shuoke Crystal Co., Ltd.) is ultrasonically cleaned for 15 minutes with anhydrous ethanol and deionized water respectively, and a DC power analyzer (model KEYSIGHT, N6705B) is used as an electrochemical etching power source, the cleaned SiC single crystal is used as an anode, and a graphite sheet is used as a cathode. The SiC single crystal is anodized in a uniformly mixed etching solution of C2H5OH, HF and H2O2 (volume ratio 6:6:1). Anodization etching includes two steps: the first step is to remove the cap layer, first apply a pulse voltage of 19V (T 0.8s =19V 0.4s +0V 0.4s ) for cap layer etching for 0.9 min, with a pulse period of 0.8 s and a dwell time of 0.4 s. Then the voltage was adjusted to 30 V, and the cap layer was stripped for 0.1 min at a constant voltage of 30 V (T 0.8s =19V 0.4s +19V 0.4s ); then the second step of continuous periodic etching is performed, and a pulse voltage of 19V is applied (T 0.8s =19V 0.4s +0V 0.4s ), the etching time lasts for 10 minutes, the pulse period is 0.8 seconds, and the dwell time is 0.4 seconds. After the etching is completed, the semi-finished photoanode is ultrasonically cleaned with anhydrous ethanol and deionized water respectively, and then placed in a constant temperature drying oven at 60°C for 5 minutes to obtain a SiC photoanode semi-finished product. The pore size of the SiC photoanode semi-finished product is 70nm.

[0053] The preparation of the SiC@C integrated composite photoanode is as follows: 200 mg PMMA is placed as a carbon source in the high temperature zone of a double-temperature zone tubular furnace, a SiC photoanode semi-finished product with a size of 0.5 cm × 1.5 cm is vertically fixed in a porcelain boat and placed in the low temperature zone of the double-temperature zone tubular furnace, and under a 400 sccm nitrogen atmosphere, the high temperature zone is heated from room temperature to 160°C at a rate of 1°C / min and kept warm for 15 min, while the low temperature zone is simultaneously heated to 50°C at the same time and also kept warm for 15 min, and then cooled with the furnace to obtain a SiC@C integrated composite photoanode.

[0054] The structure of the SiC@C integrated composite photoanode prepared above was characterized by scanning electron microscopy (FESEM, S-4800, Hitachi, Japan). Figure 1 As shown in FIG. 1 , it can be seen that the composite photoanode coated with the carbon nanolayer for 15 min still has a uniform nanopore structure with a pore size of about 50 nm; the transmission electron microscopy (TEM) image of the nanopore structure of the composite photoanode for 15 min is shown in FIG. Figure 2As shown, it can be seen that the average thickness of the amorphous carbon nanolayer on the surface of the nanopore structure is about 2.67 nm.

[0055] The phase and composition of the SiC@C integrated composite photoanode prepared above were characterized by Raman spectrometer (Raman, Renishaw inVia, UK). Figure 3 As shown, the Raman characteristic peaks in different regions of the composite photoanode are consistent, and all show Raman characteristic peaks of amorphous carbon in different hybrid states, indicating the uniform deposition of carbon nanofilm on the SiC photoanode.

[0056] The photoelectrocatalytic performance of the prepared SiC@C integrated composite photoanode was characterized using a Chenhua electrochemical workstation (CHI-660D) under the irradiation of simulated sunlight from a xenon lamp. The linear voltammetric scan curve is shown in Figure 4 As shown in the figure, the photocurrent density is 5.0mA / cm 2 , the starting potential is -0.049V. Figure 5 As shown, the light conversion efficiency reaches 2.67%, indicating that the prepared SiC@C integrated composite photoanode has excellent photoelectrocatalytic performance.

[0057] Example 2

[0058] Compared with Example 1, the difference is that the holding time in the dual-temperature zone tubular furnace is 5 minutes. Figure 6 The SEM image of the SiC@C integrated composite photoanode shown in the figure shows that the SiC@C integrated composite photoanode coated with the carbon nanolayer for 5 minutes still retains a uniform nanopore array structure with a pore size of 60nm. The photoelectrocatalytic performance of the SiC@C integrated composite photoanode was characterized, and the linear voltammetric scanning curve is shown in Figure 7 As shown in the figure, the photocurrent density is 3.84mA / cm 2 , the starting potential is -0.066V. Figure 8 As shown, the light conversion efficiency of the sample reaches 1.95%, indicating that the SiC@C integrated composite photoanode sample prepared in this example also has excellent photoelectrocatalytic performance.

[0059] Example 3

[0060] Compared with Example 1, the difference is that the holding time in the dual-temperature zone tube furnace is 10 minutes. The SiC@C integrated composite photoanode coated with a 10-minute carbon nanolayer still retains a uniform nanopore array structure with a pore size of 53nm. The photoelectrocatalytic performance of the SiC@C integrated composite photoanode was characterized, and its light conversion efficiency reached 2.34%. The prepared SiC@C integrated composite photoanode had a certain attenuation in the photoelectrocatalytic performance of the composite photoanode due to the short carbon deposition time resulting in a too thin carbon nanolayer.

[0061] Example 4

[0062] Compared with Example 1, the difference is that the holding time in the dual-temperature zone tubular furnace is 25 minutes. Fig. 9 The SEM image of the SiC@C integrated composite photoanode shown in the figure shows that the SiC@C integrated composite photoanode coated with the carbon nanolayer for 25 minutes still retains a uniform nanopore array structure with a pore size of 48nm. The photoelectrocatalytic performance of the SiC@C integrated composite photoanode was characterized, and the linear voltammetric scanning curve is shown in Fig.10 As shown in the figure, the photocurrent density is 3.75mA / cm 2 , the starting potential is 0.034V. Fig.11 As shown, the light conversion efficiency of the sample reaches 2.10%, indicating that the SiC@C integrated composite photoanode prepared in this example also has excellent photoelectrocatalytic performance.

[0063] Example 5

[0064] Compared with Example 1, the difference is that the holding time in the dual-temperature zone tube furnace is 30 minutes. The SiC@C integrated composite photoanode coated with a 30-minute carbon nanolayer still retains a uniform nanopore array structure with a pore size of 41nm. The photoelectrocatalytic performance of the SiC@C integrated composite photoanode was characterized, and its light conversion efficiency reached 1.98%. The prepared SiC@C integrated composite photoanode has a certain attenuation in the photoelectrocatalytic performance of the composite photoanode due to the short carbon deposition time resulting in a too thin carbon nanolayer.

[0065] Example 6

[0066] Compared with Example 1, the difference is that the temperature of the low temperature zone is 70° C. The photoelectrocatalytic performance of the SiC@C integrated composite photoanode is characterized, and its light conversion efficiency reaches 1.86%.

[0067] Comparative Example 1

[0068] Compared with Example 1, the difference is that the SiC photoanode semi-finished product is directly subjected to the photoelectrocatalytic performance characterization, and its photocurrent density is 2.5 mA / cm 2 , the starting potential is 0.019V.

[0069] Comparative Example 2

[0070] Compared with Example 1, the difference is that the holding time in the dual-temperature zone tubular furnace is 35 minutes. Fig.12The SEM image of the SiC@C integrated composite photoanode shown in the figure shows that the SiC@C integrated composite photoanode coated with the carbon nanolayer for 35 minutes still retains a uniform nanopore array structure with a pore size of 30nm. The photoelectrocatalytic performance of the SiC@C integrated composite photoanode was characterized, and the linear voltammetric scanning curve is shown in Fig.13 As shown in the figure, the photocurrent density is 4.35mA / cm 2 , the starting potential is -0.044V. Fig.14 As shown, the light conversion efficiency reaches 1.91%. Due to the excessive carbon deposition time, the pore size of the nanopore structure of the prepared SiC@C integrated composite photoanode becomes smaller, and the photoelectrocatalytic performance of the composite photoanode is attenuated to a certain extent.

[0071] Comparative Example 3

[0072] Compared with Example 1, the difference is that the holding time in the dual-temperature zone tube furnace is 2 minutes. The 2-minute carbon nanolayer-coated SiC@C integrated composite photoanode still retains a uniform nanopore array structure with a pore size of 65nm. The photoelectrocatalytic performance of the SiC@C integrated composite photoanode was characterized, and its light conversion efficiency reached 1.20%. The prepared SiC@C integrated composite photoanode had a certain attenuation in the photoelectrocatalytic performance of the composite photoanode due to the short carbon deposition time resulting in a too thin carbon nanolayer.

[0073] Comparative Example 4

[0074] Compared with Example 1, the difference is that the reaction is carried out in a single-temperature zone tube furnace at a temperature of 160° C. The light conversion efficiency reaches 0.81%.

[0075] In summary, the SiC@C integrated composite photoanode of the present invention has an amorphous carbon nano-thin layer deposited on its surface, which acts as a hole transport storage layer and is tightly coated on the surface of the SiC nano-pore wall, thus having an excellent photocatalytic effect.

[0076] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A SiC@C integrated composite photoanode, characterized in that: The SiC@C integrated composite photoanode comprises a SiC nano-hole array layer and a carbon nano-thin layer deposited on the surface thereof; The method for preparing the SiC@C integrated composite photoanode comprises: subjecting polymethyl methacrylate and a SiC photoanode semi-finished product to chemical vapor deposition in a dual-temperature zone tubular furnace; The polymethyl methacrylate is located in the high temperature zone of the dual-temperature zone tubular furnace, and the SiC photoanode semi-finished product is located in the low temperature zone of the dual-temperature zone tubular furnace, and both are maintained for 5-30 minutes after the temperature is raised; The temperature of the high temperature zone is 140-190°C, and the temperature of the low temperature zone is 40-65°C; the heating time of the high temperature zone and the low temperature zone is the same; the heating speed of the high temperature zone is 0.5-2°C / min.

2. The SiC@C integrated composite photoanode according to claim 1, characterized in that: The pore size distribution of the SiC@C integrated composite photoanode is 40-60 nm; the pore size distribution of the nano-hole array structure without depositing the carbon nano-thin layer is 50-70 nm.

3. The SiC@C integrated composite photoanode according to claim 1, characterized in that: The thickness of the carbon nanofilm is 2-5 nm.

4. The SiC@C integrated composite photoanode according to claim 1, characterized in that: The carbon nanosheet is amorphous carbon.

5. A method for preparing the SiC@C integrated composite photoanode according to claim 1, characterized in that: The method for preparing the SiC@C integrated composite photoanode comprises: subjecting polymethyl methacrylate and a SiC photoanode semi-finished product to chemical vapor deposition in a dual-temperature zone tubular furnace; The polymethyl methacrylate is located in the high temperature zone of the dual-temperature zone tubular furnace, and the SiC photoanode semi-finished product is located in the low temperature zone of the dual-temperature zone tubular furnace, and both are maintained for 5-30 minutes after the temperature is raised; The temperature of the high temperature zone is 140-190°C, and the temperature of the low temperature zone is 40-65°C; the heating time of the high temperature zone and the low temperature zone is the same; the heating speed of the high temperature zone is 0.5-2°C / min.

6. The method for preparing the SiC@C integrated composite photoanode according to claim 5, characterized in that: The amount of polymethyl methacrylate added is 180-220 mg, and the size of the SiC photoanode semi-finished product is (0.5-1.5) cm×1.5 cm.

7. The method for preparing the SiC@C integrated composite photoanode according to claim 5, characterized in that: The preparation of the SiC photoanode semi-finished product comprises: etching and stripping the cap layer and etching the nano-hole structure in sequence on the cleaned 4H-SiC single crystal and graphite sheet in an etching solution.

8. The method for preparing the SiC@C integrated composite photoanode according to claim 7, characterized in that: The etching solution is a mixed solution of HF, C2H5OH and H2O2 in a volume ratio of (5-7):(5-7):

1.

9. The method for preparing the SiC@C integrated composite photoanode according to claim 7, characterized in that: The cap layer etching voltage is a pulse voltage of 20-22V, the duration is 0.8-0.9min, the application cycle is 0.7-0.9s, and the dwell time is 1 / 2 of the application cycle. The subsequent stripping process applies a constant voltage of 28-32V, the duration is 0.1-0.2min; the nanopore structure etching is continuous cycle etching, the etching voltage is a pulse voltage of 18-20V, the application cycle is 0.7-0.9s, the dwell time is 1 / 2 of the application cycle, and the duration is 9-11min.

10. Use of the SiC@C integrated composite photoanode as claimed in claim 1 in the field of photocatalysis.

Citation Information

Patent Citations

  • Carbon quantum dot-modified bismuth tungstate / ordered macroporous fluorine-doped tin oxide composite photocatalyst, and preparation method and application thereof

    CN110252352A

  • Preparation method and application of 4H-SiC integrated self-supporting photoanode

    CN111188082A